In Growing Toenail Treatment using Carbon Dioxide Laser - Ibrahim, Ahmed W.; Jawad, Hussien A. (Iraqi Journal of Laser, 2019)
An ingrowing toenail is a common problem affecting mainly adolescents and young adults, with a male predominance of 3:1. The disorder generally occurs in big toes. It is painful and often chronic and it affects work and social activities. Most patients initially complain of pain and later discharge, infection and difficulty in walking occur. The Objectives: The purpose of the study was to evaluate the efficacy and safety of (10600nm) CO2 laser in the treatment of ingrowing toe nail. Patients, Materials & Methods: This study was done in laser medicine research clinics from July 2013 to the end of December 2013; 10 patients including 7(70%) males and 3 (30%) females with age ranging from 18 years to 70 years with mean age of 44 years old. The details of the procedure were explained verbally to the patients. Patients were examined and evaluated clinically and prepared for surgery. A CO2 continuous wave 1-40W laser emitted at 10600 nm; the laser was delivered via an articulated arm. Laser was used for cutting the nail and vaporization of the underlying germinal layer (matrix). Results: The preliminary clinical findings included sufficient hemostasis, coagulation properties and precise incision margin with all of the surgical procedure. The postoperative advantages, i.e., lack of pain, bleeding, infection and, recurrence the good wound healing and overall satisfaction were observed in the clinical application of laser in treatment of ingrowing toenail. Conclusion: The clinical application of the CO2 (10600 nm) laser in surgical procedures prove to be of beneficial effect for daily practice. It can be considered practical, effective and easy to use, and it offers a safe, acceptable, and impressive alternative for conventional techniques of surgical treatment of in growing toenail.